STRENGTHENING ASEAN CENTRALITY WITHIN THE INDO-PACIFIC REGION - Siahaan, Sereffina Yohanna Elisabeth; Risman, Helda (PEOPLE: International Journal of Social Sciences, 2020)
The emergence of Indo-Pacific terminology leads to an interesting path of cooperation within the arena between countries. The Indo-Pacific region, marked by the cross-geography of the Indian and Pacific Oceans, is home to some of the most diverse populations, international trade and global exports. Some countries have been questioned about the importance of this area, namely the U.S., Australia, Japan, People's Republic of China (PRC), India, and the states in the Southeast Asia. A few sea districts, such as the South China Ocean, have contended most over the Indo-Pacific, and the Indian sea over the Malacca Strait has been a source of expanding oceanic security dangers. This paper focuses upon the challenges of the Indo-Pacific region, non-traditional oceanic threats like piracy and particularly related to the maritime strife, namely South China Sea dispute. The method used on this research is a qualitative method with a analytical descriptive approach. The purpose of this study is to discuss the ASEAN centrality in region as a form of maritime security cooperation without any country feeling left behind to accommodate all nations within the region. This new nomenclature reflects a glimpse of ASEAN's spirit as an ecosystem of peace, stability, and prosperity, including in addressing the region's inclusiveness and connectivity. The conclusion of the study indicates that ASEAN’s initiative needs to be addressed within the Indo-Pacific if the idea is increasingly institutionalized and major powers collaborate more closely.